Invertase Suc2-mediated inulin catabolism is regulated at the transcript level in Saccharomyces cerevisiae. Issue 1 (December 2015) - Yang, Fan; Liu, Zhi-Cheng; Wang, Xue; Li, Li-Li; Yang, Lan; Tang, Wen-Zhu; Yu, Zhi-Min; Li, Xianzhen
Abstract Background Invertase Suc2 was recently identified as a key hydrolase for inulin catabolism inSaccharomyces cerevisiae, whereas the Suc2 activity degrading inulin varies greatly in differentS. cerevisiae strains. The molecular mechanism causing such variation remained obscure. The aim of this study is to investigate how Suc2 activity is regulated inS. cerevisiae . Results The effect ofSUC2 expression level on inulin hydrolysis was investigated by introducing differentSUC2 genes or their corresponding promoters inS. cerevisiae strain BY4741 that can only weakly catabolize inulin. Both inulinase and invertase activities were increased with the risingSUC2 expression level. Variation in the promoter sequence has an obvious effect on the transcript level of theSUC2 gene. It was also found that the high expression level ofSUC2 was beneficial to inulin degradation and ethanol yield. Conclusions Suc2-mediated inulin catabolism is regulated at transcript level inS. cerevisiae . Our work should be valuable for engineering advanced yeast strains in application of inulin for ethanol production.